On The Impossibility Of Empirical Controls Of Scientific Theories – From The Point Of View Of A Psychologist - Micko, Hans Christoph (Foundations of science, 2004)
Standard considerations of philosophy of science are reformulated in psychological terms and arguments, suggesting a fundamental change in life perspective: subjective experiences or introspective data are subject to motivational biases and therefore not admitted as objective empirical facts in science, However, we never experience objects or events of the external world, i.e., so called objective facts, but exclusively subjective percepts or mental events. They are merely assumed to, but may or may not be accurate or distorted mental representations of objects or events of an external world. Accordingly, the latter are theoretical constructs, i.e., constructs of the fictitious but most successful predictive (implicit) theory, called “external world”, which seems to be constructed from regularities observed in mental events and serves as a reference fiction for, erroneously called empirical, tests of predictions of scientific theories.